Benefit of a staged in‐hospital revascularization strategy in hemodynamically stable patients with ST‐segment elevation myocardial infarction and multivessel disease: Analyses by risk stratification. Issue 6 (22nd June 2020) - Kim, Min Chul; Bae, SungA; Ahn, Youngkeun; Sim, Doo Sun; Hong, Young Joon; Kim, Ju Han; Jeong, Myung Ho; Kim, Hyo‐Soo; Chae, Shung Chull; Cha, Kwang Soo; ,
Abstract: Aims: The proper timing and indication of revascularization for a non‐culprit artery in patients with ST‐segment elevation myocardial infarction (STEMI) and multivessel disease (MVD) without cardiogenic shock remains controversial. Methods and Results: This multicenter study included patients with STEMI and MVD without cardiogenic shock. Data were analyzed at 3 years according to the percutaneous coronary intervention (PCI) strategy: immediate multivessel revascularization (MVR) ( n = 351), stepwise MVR ( n = 510), and culprit‐only PCI ( n = 1, 142). The primary outcome was all‐cause mortality. The stepwise MVR group had a lower risk of all‐cause death. The results were consistent after multivariate regression, propensity‐score matching, inverse probability weighting, and Bayesian proportional hazards modeling. In subgroup analyses stratified by the Global Registry of Acute Coronary Events score, stepwise MVR also lowered the risk of all‐cause death compared to culprit‐only PCI and immediate MVR in high risk patients but not in patients at low to intermediate risk. Conclusions: In patients with STEMI and MVD without cardiogenic shock, in‐hospital stepwise MVR was associated with a lower risk of all‐cause death than culprit‐only PCI or immediate MVR, particularly in the high‐risk subgroup.